CORRELATION BETWEEN ANEMIA EDUCATION AND ADHERENCE TO IRON SUPPLEMENTATION THERAPY AND HEMOGLOBIN LEVELS IN PREGNANT WOMEN AT PADASUKA AND PAGARSIH COMMUNITY HEALTH CENTER BANDUNG CITY - Utami Ayungga Putri, Suci
Anemia is a condition in which hemoglobin (Hb) level is lower than normal, in pregnant women can increase morbidity and mortality of mother and children, adherence to iron supplement therapy (TTD) and regulating balanced nutritional food patterns, especially iron (Fe) intake during pregnancy are important in maintaining normal hemoglobin (Hb) levels. This study aims to determine the effect of education on pregnant women’s knowledge of iron deficiency anemia, adherence to iron supplement therapy (TTD), iron (Fe) intake, and hemoglobin (Hb) levels of pregnant women and the relationship between these variables. This research is an experimental study of one group pre-post test with data collection through questionnaire interviews and laboratory examination of hemoglobin (Hb) levels. The research was conducted in January – March 2023 at UPT Puskesmas Padasuka and Pagarsih, Bandung City. Data on adherence to iron supplement therapy (TTD), iron (Fe) intake, and knowledge of iron deficiency anemia were obtained from questionnaires. Brief Medication Questionnaire (BMQ) for adherence to iron supplement therapy (TTD), Food Frequency Questionnaire (FFQ) to iron (Fe) intake data, and as well as a questionnaire that has been used in previous studies for knowledge of iron deficiency anemia. The results showed that education had a positive effect on knowledge of iron deficiency anemia in pregnant women (p = 0,011), adherence to iron supplement therapy (TTD) ( p = 0,006), intake of iron (Fe) (p = 0,001), and hemoglobin (Hb) levels pregnant women (p = 0,011) and obtained a positive and very strong relationship between knowledge of iron deficiency anemia pregnant women with adherence to iron supplement therapy (TTD) (p<0,001 dan r = 0,957), knowledge of iron deficiency anemia pregnant women with intake iron (Fe) (p<0.001 and r = 0.972), knowledge of iron deficiency anemia pregnant women with hemoglobin (Hb) levels (p<0.001 and r = 0.988), adherence to iron supplement therapy (TTD) with iron intake ( Fe) (p<0.001 and r = 0.933), adherence to iron supplement therapy (TTD) with hemoglobin (Hb) levels (p<0.001 and r = 0.948), and intake of iron (Fe) with hemoglobin (Hb) levels (p <0.001 and r = 0.978). However, education still needs to be carried out periodically to get optimal educational effectiveness.